Applying to College: You Can Do It! - Danielle Scott; Heidi Liss Radunovich (EDIS, 2007)
FCS2272, a 6-page fact sheet by Danielle Scott and Heidi Liss Radunovich, is intended for high school students and others wanting to apply to college for the first time. It walks applicants through the steps necessary to apply to college and provides useful information on choosing a school, testing, and completing applications. Published by the UF Department of Family, Youth and Community Sciences, April 2007.